Comportamento sintático-semântico de verbos de movimento com trajetória no português brasileiro – subclasse verbal com direção não especificada - Poll, Talita Veridiana Hack (2019)
This research looks into the semantic and syntactic behavior of motion verbs with path which do not specify direction in Brazilian Portuguese (PT-BR). The theoretical assumptions that support this work are linked to lexical studies, especially to lexical semantics, and also to cognitive semantics. Our goal is to carry out a description of the grammatical behavior of the verbs of motion with path without a lexically implied direction. To do so, we performed the delimitation of the verbal class of the verbs with motion and path of the PT-BR, from the identification of the root of motion and path lexicalized by the verbal class. The analysis of semantic properties lexicalized by the path verbs that do not specify direction of the PT-BR made it possible to observe that the meaning of motion verbs with path that do not lexicalize direction (verbs type atravessar) do not include a specification of the direction of motion, but maps a movement along a path. Also, when applied the adjunction test we developed, we observed that the verbs that lexicalize movement by an unspecified path (verbs type atravessar) present a different semantic structure from that of verbs that lexicalize movement by a path with specified direction (verbs type subir), with regard to the determination of direction. In addition, we analyzed the meaning of motion verbs with path that do not lexicalize direction, using the lexical meaning in primitive predicates decomposition metalanguage, based on the proposal of Rappaport-Hovav and Levin (2010). Starting from the performed analysis, we have developed a new verification test for path verbs, proposing the lexical representation structure [x BECOME AT <RESULT-PLACE>] as a better way to represent these verbs, as this structure specifies the information of the resulting place expressed by them. This analysis allowed us to show that the verbs with motion and path of the PT-BR lexicalize the direction in different ways, and that the verbs type atravessar can be described by the same rules of lexical representation as the verbs type subir, since the information captured by the representation structure is the one of displacement by a trajectory. The results indicate that the motion verbs with path are heterogeneous regarding lexicalization of direction, but, nevertheless, they present the common sense of resulting place, the effect of the displacement in the physical space. In this regard, it was concluded that the semantic element of direction is not a grammatically relevant property, therefore, it would not impact in the lexical representation of the motion verbs with path that do not specify direction.